2004
DOI: 10.1063/1.1811793
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN ∕ GaN metal-oxide-semiconductor heterostructure field-effect transistor with oxidized Ni as a gate insulator

Abstract: We fabricated the AlGaN∕GaN metal-oxide-semiconductor heterostructure field-effect transistor (MOSHFET) using the oxidized Ni(NiO) as a gate oxide and compared electrical properties of this device with those of a conventional AlGaN∕GaN heterostructure field-effect transistor (HFET). NiO was prepared by oxidation of Ni metal of 100Å at 600°C for 5min in air ambient. For HFET and MOSHFET with a gate length of 1.2μm, the maximum drain currents were about 800mA∕mm and the maximum transconductances were 136 and 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…8 Recently, NiO formed by thermal oxidation of Ni films has been proposed as the gate insulator in AlGaN/GaN HEMTs. 9 However, the thermal oxidation of Ni films can proceed through different stages 10,11 and can result into the formation of voids in the oxide layer. 10 This latter severely compromise the devices reliability and a uniform and epitaxial layer would certainly be preferred.…”
mentioning
confidence: 99%
“…8 Recently, NiO formed by thermal oxidation of Ni films has been proposed as the gate insulator in AlGaN/GaN HEMTs. 9 However, the thermal oxidation of Ni films can proceed through different stages 10,11 and can result into the formation of voids in the oxide layer. 10 This latter severely compromise the devices reliability and a uniform and epitaxial layer would certainly be preferred.…”
mentioning
confidence: 99%
“…[1][2][3][4] The Schottky based GaN highelectron-mobility transistors (HEMTs) are suffering from large gate leakage current (I gLeak ). To reduce the I gLeak , variety of gate oxides/insulators such as electron beam (EB) evaporated SiO 2 , 5,6) plasma enhanced chemical vapor deposited (PECVD) SiO 2 , 5,7) Photo-CVD SiO 2 , 8) PECVD-Si 3 N 4 , 5,9) AlN, 10,11) 10) native oxide, 12) nickel oxide 13) and AlON 14) have been realized to get high quality metal-oxide-semiconductor (MOS) or metal-insulator-semiconductor (MIS) structures. High breakdown voltage with low I gLeak have been reported on GaN-based MOS field-effect-transistors (FETs)/MISFETs and AlGaN/ GaN MOS and MIS heterostructure field-effect transistors (HFETs) using PECVD-SiO 2 and -Si 3 N 4 as gate insulators.…”
mentioning
confidence: 99%
“…18) Till now, researchers have demonstrated low extrinsic transconductance (g mmax ) values of metal-oxide-semiconductor high-electron-mobility transistors (MOSHEMTs) or MOSHFETs. [8][9][10][11][12][13][14][15][16][17] Recently, Maeda et al 19) demonstrated high g mmax of 280 mS/mm from thin bilayer Al 2 O 3 /Si 3 N 4 insulating gate layers MOSHEMTs. Comparatively good quality EB evaporation SiO 2 with low interface state density on n-GaN has been realized and reported elsewhere.…”
mentioning
confidence: 99%
“…More specifically, at the reverse gate voltage of -10 V, the leakage current density of Ni/Rh/Au is ~0.0082 mA/mm, 85% less compared to that of the Ni/Au gate device (0.0531 mA/mm). This reduction of the leakage current may result from the decreased interfacial defects, as well as the existence of NiO [12,13]. It should be mentioned that owing to the small gate dimension (2 × 45 μm 2 ), the beneficial chemical reactions (removal of interfacial defects / formation of NiO), which help enhance the contact performance, at the gate metal/substrate interface may not be uniform.…”
Section: Resultsmentioning
confidence: 99%